A study on the dynamic comparison of logistics industry's correlation effects in China - Shaohua Yi; Jie Xie (China Finance and Economic Review, 2017)
Background: Entering the middle and late period of 1990s, the logistics industry has been keeping high-speed growth along with China's continuously increasing economic level. As a basic and strategic industry, the logistics industry is closely linked with and influenced by other industries while influencing them. It plays an irreplaceable role in ensuring smooth operation of the national economy and satisfying the demand of consumers. Its development level directly affects that of the national economy. Methods: With input-output tables from 1997 to 2010, the input-output model was used to measure the association effect between the logistics industry and its related industries and to calculate the dynamic degree of influence logistics industry exerts on relevant industries at the different periods. Results: According to the input-output analysis, we found results as follows. (1) the status of logistics industry remains to be further promoted. (2) The logistics industry turns into one with 'low added value and strong leading force.' (3) Industrial logistics is the main trend while logistics of service industry change. (4) The logistics industry is closely linked with the second industry. Conclusions: To promote the sustained healthy development of logistics industry and give full play to the role of logistics industry in the national economy, the authors then put forward countermeasures and suggestions: (1) Develop third-party logistic in order to promote the socialization and specialization level of logistics distribution. (2) Speed up the development of electronic business logistics, set up reasonable layout of transportation infrastructure, and build entitative logistics network. (3) Accelerate the logistics informatization and standardization and improve management and service levels of logistics enterprises.
Keywords: 330; Logistics industry; Correlation effect; Dynamic comparison